Exosome-drug conjugates delivery: a promising strategy for ameliorating the pharmacokinetic profile of artesunate - Wang, Da; Bai, Yunfei; Cheng, Guogang; Shen, Shengqiang; Xiao, Gengwu; Ma, Demei; Zhao, Ganggang; Chen, Wei; Li, Tianshi; Zhang, Litao; Ge, Xiaohu (Frontiers in Bioengineering and Biotechnology, 2024)
Artesunate (ATS) is considered the most widely employed artemisnin derivative in the treatment of Plasmodium falciparum malaria. However, poor solubility and low bioavailability of ATS limit its further clinical application. Herein, we developed a new strategy based on the exosome-drug conjugation (EDC) using the milk-derived exosomes for ATS delivery. The exosome-ATS conjugates (EACs) which formed via a facile bio-conjugation of ATS to the exosomal surface, have been demonstrated to be able to not only boost the solubility and bioavailability of ATS but also enable a sustained-release of ATS from exosomes. Maximal improvement of 71.4-fold in the solubility of ATS was attained by EACs. The corresponding entrapment efficiency and drug loading capacity were found to be 90.3% and 73.9% for EACs, respectively. Further, in vivo pharmacokinetics study manifested that maximum 2.6-fold improved bioavailability of ATS was achieved by oral delivery of EACs. Moreover, EACs displayed a distinct sustained-release profile of maximum 36.2-fold prolonged half-life of ATS via intravenous delivery. We reported that for the first time the administration of EACs could be a potential drug delivery strategy aimed at ameliorating the pharmacokinetic profile of ATS based on our encouraging results and hoped that our work opened up a new avenue for the development of EDC delivery system.